Akuisisi Bahasa Pertama Pada Anak Usia 5 Tahun - Riana Anjarsari (Lembaga Pengembangan Kinerja Dosen, 2024)
Discussion of language acquisition cannot be separated from the factors that influence it. Language acquisition is a process of acquiring a child's first language without any special learning about language. A child will only respond to utterances that are often heard from the surrounding environment, especially utterances from the mother. In the process of acquiring language, a child cannot be separated from communication activities involving the interlocutor. In this study researchers conducted research on language acquisition, especially on a 5 years old child. This research was conducted with the following objectives; 1) To describe language acquisition in the components of syntax acquisition, semantic acquisition, phonology acquisition, and morphology acquisition in 5 years old child; 2) To describe the factors that influence 5 years old child language acquisition. The results of this study show that language acquisition at the age of 5 a has reached four components, namely syntax acquisition, semantic acquisition, phonology acquisition, and morphology acquisition. Apart from that, there are three factors that influence the language acquisition process as follows; 1) natural factors; 2) cognitive development factors; and 3) social background factors